Self - cleaning coating - an exploration in the applications of photo - catalyst as hybrid multifunctional nanocomposite in wastewater treatment and gas conversion - Tan, Jian Wei (2015)
Photo-catalysts are widely used in many fields including wastewater treatment processes and gas conversion of pollutants to syn-gas due to its ability to make use of the most abundant renewable energy source of solar energy. As these photo-catalysts are commonly applied in powdered form for wastewater treatment, problems attributing to the reduced efficiency due to agglomeration of particles as well as difficulty in recovery and reuse surfaced. These issues need to be addressed in order to justify the continual usage of these photo-catalysts as well as balancing their economical and efficiency costs. Carbon Dioxide (CO2) emissions had risen to record levels, leading to the exacerbation of the global warming issue. The exploration of the plausibility of photo-catalyst converting it with reasonable efficiency into useful gases such as Methane (CH4) for fuel may prove to yield valuable economic and environmental benefits. This report focuses on the integration of the photo-catalyst, Copper Sulphide (CuS), with Graphene Oxide functionalised by carboxylic acid group (GO-COOH) and Silver (Ag) as hybrid multifunctional nano-composite (GO-COOH-CuS-Ag), synthesised as pure powder form and into self-cleaning coatings for exploration in the fields of wastewater treatment and gas conversion. Laboratory trials were conducted to identify the most suitable and viable method of coating the nano-composite on glass substrates followed by the degradation of Methylene Blue (MB) dye by these coatings under dark and solar simulated conditions to establish the relationship between degradation efficiency and concentration of GO-COOH-CuS-Ag applied in the coatings. Trials were also conducted to determine the efficiency of Carbon Dioxide (CO2) conversion into Methane (CH4) by pure GO-COOH-CuS-Ag powder. Results show that despite the failure of gas conversion, the coatings performed consistently in the degradation of MB showing distinct trend of increasing efficiency with larger concentration of GO-COOH-CuS-Ag used. Therefore, this signals the plausibility of application of such self-cleaning coatings in wastewater treatment in bid of eliminating the fore mentioned problems.